Bibliometric Analysis of The Field of Tafsir: A Map of The Development of Research on the Interpretation of The Qur'an and Science - Azmil Iman hartafan (Bulletin of Islamic Research, 2023)
This study aims to conduct bibliometric analysis related to the interpretation of the Qur'an and science. Bibliometric analysis techniques are used to search all publications indexed in the scopus database and the data obtained are analyzed using excel, R-studio and VOSviewer. This research method involves searching and analyzing scientific articles related to the interpretation of the Qur'an and science such as, keywords, number of publications per year, main data information, number of citations, prolific researchers, and place of publication related to this study, to provide an understanding of the development and impact of research in this field. The results of the bibiometric analysis show that the interpretation of the Qur'an and science has become an increasing subject of research in recent years as well as a significant increase in the number of publications in this field. The limitation of this study is that it only takes datasets or meta data of publications indexed in Scopus. Other national and international databases were not considered in this study. This study presents a brief overview of the literature accessible to researchers and provides recommendations for future research.